2017
DOI: 10.1177/0022034517719264
|View full text |Cite
|
Sign up to set email alerts
|

Grainyhead-like Transcription Factors in Craniofacial Development

Abstract: Craniofacial development in vertebrates involves the coordinated growth, migration, and fusion of several facial prominences during embryogenesis, processes governed by strict genetic and molecular controls. A failure in any of the precise spatiotemporal sequences of events leading to prominence fusion often leads to anomalous facial, skull, and jaw formation-conditions termed craniofacial defects (CFDs). Affecting approximately 0.1% to 0.3% of live births, CFDs are a highly heterogeneous class of developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 96 publications
0
24
0
Order By: Relevance
“…In ovarian cancer for example, GRHL2 expression counteracts epithelial to mesenchymal transition and increases the overall survival of patients 59 , 60 . Mutations in the GRHL factors are also linked to pulmonary fibrosis 66 and several craniofacial disorders 67 . We found that mammalian GRHL homologs are required for setting up the accessible epithelial chromatin landscape, and that the biochemistry of GRHL binding and nucleosome displacement are highly analogous to Drosophila .…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian cancer for example, GRHL2 expression counteracts epithelial to mesenchymal transition and increases the overall survival of patients 59 , 60 . Mutations in the GRHL factors are also linked to pulmonary fibrosis 66 and several craniofacial disorders 67 . We found that mammalian GRHL homologs are required for setting up the accessible epithelial chromatin landscape, and that the biochemistry of GRHL binding and nucleosome displacement are highly analogous to Drosophila .…”
Section: Discussionmentioning
confidence: 99%
“…Exome sequencing-based association studies have revealed several variations in human GRHL3 associated with non-syndromic CPO in almost all populations studied (Leslie et al, 2016; Mangold et al, 2016; Hoebel et al, 2017; Eshete et al, 2018) (Table 2), except in the Han Chinese (He and Bian, 2016), suggesting GRHL3 as a strong candidate gene for non–syndromic CPO. Thus, proper Grhl3 expression in the epithelium during palatogenesis seems to be crucial for normal palate formation (Carpinelli et al, 2017). In mice, a cooperative interaction has been suggested between Grhl2 and Grhl3 during primary neurulation (Box 1) (Rifat et al, 2010), and Grhl3 might act downstream of canonical Wnt signaling during neural tube closure (Kimura-Yoshida et al, 2015).…”
Section: Crosstalk Between Wnt Signaling Cell Adhesion Molecules Andmentioning
confidence: 99%
“…4). GRHL2 is in the same gene family as GRHL3, which is a transcription factor that causes syndromic forms of clefting and is associated with nonsyndromic clefting in other GWAS (Leslie et al, 2016a,b; Carpinelli et al, 2017; Peyrard-Janvid et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Applying our method to Pittsburgh Orofacial Cleft Multiethnic GWAS (Leslie et al, 2016a,b), we identified a gene (GRHL2) (not previously reported) to suggestively associate with cleft lip and palate phenotypes. GRHL2 is in the same gene family as GRHL3, which is a transcription factor that causes in syndromic forms of clefting and was found to be associated with nonsyndromic clefting in GWAS (Leslie et al, 2016a,b; Carpinelli et al, 2017; Peyrard-Janvid et al, 2014). Burden and SKAT on these same phenotypes (figure 4) failed to identify any significant or suggestive genes.…”
Section: Discussionmentioning
confidence: 99%